Measurement of the impact of micro-credit programs on poverty alleviation in Bangladesh - Billah, Md Arif (IIUC Business Review, 2022)
The main purpose of this study is to measure the impact of micro-credit programs on selected non-government organizations (NGOs) regarding poverty alleviation in Bangladesh using a purposive sample of 1000 credit borrowers. Alongside respondents' perceived change in a poverty situation, this study developed an alternative measure of poverty change based on changes in household wealth and educational attainment. This study found that the perceived change in poverty was 78.1 percent. However, the poverty change index (PI) examination indicates that around 55.6% of the respondents had successfully overcome their poverty. According to the analysis of multinomial logistic regression and two-level binary logistic regression, the amount of loan, various NGOs' performance, satisfaction level, previous loan, and micro-credit as the main instruments of asset and poverty change. Significance variation at the community level was found in this study, which means that respondents from various communities with similar attributes will demonstrat distinct impect on the evolution of the poverty situation. More research should be conducted to identify the causes of this difference to maximize the impact of microcredit. IIUC Business Review, Vol.-11, Issue-1, Dec. 2022, pp. 95-112